Resistance of Aerosolized Bacterial Viruses to Relative Humidity and Temperature - Verreault, Daniel (Appl Environ Microbiol, 2015)
The use of aerosolized bacteriophages as surrogates for hazardous viruses might simplify and accelerate the discovery of links between viral components and their persistence in the airborne state under diverse environmental conditions. In this study, four structurally distinct lytic phages, MS2 (single-stranded RNA [ssRNA]), ϕ6 (double-stranded RNA [dsRNA]), ϕX174 (single-stranded DNA [ssDNA]), and PR772 (double-stranded DNA [dsDNA]), were nebulized into a rotating chamber and exposed to various levels of relative humidity (RH) and temperature as well as to germicidal UV radiation. The aerosolized viral particles were allowed to remain airborne for up to 14 h before being sampled for analysis by plaque assays and quantitative PCRs. Phages ϕ6 and MS2 were the most resistant at low levels of relative humidity, while ϕX174 was more resistant at 80% RH. Phage ϕ6 lost its infectivity immediately after exposure to 30°C and 80% RH. The infectivity of all tested phages rapidly declined as a function of the exposure time to UVC radiation, phage MS2 being the most resistant. Taken altogether, our data indicate that these aerosolized phages behave differently under various environmental conditions and highlight the necessity of carefully selecting viral simulants in bioaerosol studies.